Internalizing Moral Education Values in Sufism: A Comparative Study of Al-Ghazali’s and Ibn Taymiyyah’s Thought - Rahmad Fauzi Lubis; Zalisman; Mursal; Baktiar Nasution (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Contemporary Islamic education faces a persistent challenge in bridging the gap between moral knowledge and moral practice, as moral instruction often remains cognitive and formalistic without leading to meaningful character transformation. This study aims to comparatively analyze the thoughts of Imam al-Ghazali and Ibn Taymiyyah on the internalization of moral education values in Sufism, with a focus on their epistemological foundations, mechanisms of internalization, and educational implications. Employing a qualitative library research design, this study draws on primary classical texts and recent scholarly literature, analyzed through qualitative content analysis and comparative synthesis. The findings reveal that al-Ghazali conceptualizes moral internalization as a process of inward transformation grounded in tazkiyat al-nafs, spiritual discipline, and the cultivation of the heart, whereas Ibn Taymiyyah emphasizes normative alignment through the purification of tawhid, the strengthening of faith, and disciplined adherence to the Qur’an and Sunnah. While differing in methodological emphasis, both perspectives converge in viewing morality as an integrated expression of inner disposition and outward action. This study proposes a dual-process model of moral internalization that integrates inward spiritual transformation with normative discipline as a comprehensive framework for moral education. The study contributes theoretically by offering an integrative conceptual model and practically by providing a foundation for designing value-based educational practices that address the limitations of purely cognitive approaches. These findings highlight the need for a balanced educational paradigm that fosters both inner awareness and consistent moral action in contemporary Islamic education.